Risk of SARS-CoV-2 reinfections in children: a prospective national surveillance study between January, 2020, and July, 2021, in England. (June 2022) - Mensah, Anna A; Campbell, Helen; Stowe, Julia; Seghezzo, Giulia; Simmons, Ruth; Lacy, Joanne; Bukasa, Antoaneta; O'Boyle, Shennae; Ramsay, Mary E; Brown, Kevin; Ladhani, Shamez N
Summary: Background: Reinfection after primary SARS-CoV-2 infection is uncommon in adults, but little is known about the risks, characteristics, severity, or outcomes of reinfection in children. We aimed to assess the risk of SARS-CoV-2 reinfection in children and compare this with the risk in adults, by analysis of national testing data for England. Methods: In our prospective, national surveillance study to assess reinfection of SARS-CoV-2 in children in England, we used national SARS-CoV-2 testing data to estimate the risk of reinfection at least 90 days after primary infection from Jan 27, 2020, to July, 31, 2021, which encompassed the alpha (B.1.1.7) and delta (B.1.617.2) variant waves in England. Data from children up to age 16 years who met the criteria for reinfection were included. Disease severity was assessed by linking reinfection cases to national hospital admission data, intensive care admission, and death registration datasets. Findings: Reinfection rates closely followed community infection rates, with a small peak during the alpha wave and a larger peak during the delta wave. In children aged 16 years and younger, 688 418 primary infections and 2343 reinfections were identified. The overall reinfection rate was 66·88 per 100 000 population, which was higher in adults (72·53 per 100 000) than children (21·53 per 100 000). The reinfection rate after primary infection was 0·68% overall, 0·73% in adults compared with 0·18% in children age younger than 5 years, 0·24% in those aged 5–11 years, and 0·49% in those aged 12–16 years. Of the 109 children admitted to hospital with reinfection, 78 (72%) had comorbidities. Hospital admission rates were similar for the first (64 [2·7%] of 2343) and second episode (57 [2·4%] of 2343) and intensive care admissions were rare (seven children for the first episode and four for reinfections). There were 44 deaths within 28 days after primary infection (0·01%) and none after reinfection. Interpretation: The risk of SARS-CoV-2 reinfection is strongly related to exposure due to community infection rates, especially during the delta variant wave. Children had a lower risk of reinfection than did adults, but reinfections were not associated with more severe disease or fatal outcomes. Funding: UK Health Security Agency.